THE INFLUENCE OF BRAND IMAGE, PROMOTION AND SERVICE QUALITY ON CUSTOMER LOYALTY OF AL INSANI UMROH TRAVEL IN SIDOARJO - Rakha Alvin Rahadianto; Siti Istikhoroh; Untung Lasiyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Indonesia's Umrah travel sector is experiencing swift expansion within the country's bustling tourism landscape. Given Indonesia's sizable Muslim populace, the annual demand for Umrah pilgrimage remains consistently high. Organizing travel aims to provide guidance, service and protection to the congregation. The aim of this study is how customer loyalty affects brand image, promotion and service quality for Al Insani Sidoarjo Umrah travel. The quantitative research method is one that is used. The population of this research consists of Al Insani Sidoarjo Umrah travel customers. A total of 112 people were used as samples, namely as participants. Samples were taken using purposive sampling technique. Instrument testing, hypothesis testing, multiple linear regression analysis, and classical assumption testing via the SPSS version 22 application are several data analysis methodologies. The results show that the variables brand image, promotion and service quality partially have a positive and significant impact on the loyalty of Umrah Al Insani Sidoarjo travel customers. Then brand image, promotion, service quality simultaneously have a positive and significant impact on customer loyalty of Al Insani Sidoarjo Umrah travel.